Cationic curdlan: Synthesis, characterization and application of quaternary ammonium salts of curdlan. (5th June 2015) - Suflet, Dana M.; Popescu, Irina; Pelin, Irina M.; Nicolescu, Alina; Hitruc, Gabriela
Highlights: Water-soluble curdlan derivatives containing quaternary ammonium groups. Studies regarding the influence of some reaction conditions (temperature, times, or molar ratio) on the degree of substitution. Polyelectrolyte complexes based on the derivatives with the same polysaccharidic chain (curdlan). Abstract: Water-soluble curdlan derivatives containing quaternary ammonium groups with a degree of substitution up to 0.15 were synthesized using different cationic agents in alkaline medium. The chemical structure of curdlan derivatives was confirmed by FTIR, 13 C and 1 H NMR spectroscopy. The influence of some reaction conditions (temperature, time, and molar ratio) on the degree of substitution and the viscosimetic behaviour were studied. The degree of substitution increased with the amount of the cationization agent per anhydroglucose unit and was higher when the glycidyl reagents were used, compared with the case when the reagents contained chloro-hydroxypropyl groups. The viscosity behaviour of these new derivatives of curdlan in aqueous solutions and the values of intrinsic viscosities calculated using different semi-empirical equations denote a high hydrodynamic dimension of the macromolecular coils. The interaction of these cationic curdlan derivatives with an anionic curdlan (monobasic curdlan phosphate) was studied in situ by turbidimetric measurements and after 24 h by optical density and dynamic light scattering. The formation of polyelectrolyte complexes was influenced by the degree of substitution, the nature of the quaternary substituent, and by the ionic strength of the aqueous solution. The morphology of the polyelectrolyte complexes particles in dry state was examined by atomic force microscopy.